Jac1, a mitochondrial J-type chaperone, is involved in the biogenesis of Fe/S clusters in Saccharomyces cerevisiae - Voisine, Cindy (The National Academy of Sciences, 2001)
A minor Hsp70 chaperone of the mitochondrial matrix of Saccharomyces cerevisiae, Ssq1, is involved in the formation or repair of Fe/S clusters and/or mitochondrial iron metabolism. Here, we report evidence that Jac1, a J-type chaperone of the mitochondrial matrix, is the partner of Ssq1 in this process. Reduced activity of Jac1 results in a decrease in activity of Fe/S containing mitochondrial proteins and an accumulation of iron in mitochondria. Fe/S enzyme activities remain low in both jac1 and ssq1 mutant mitochondria even if normal mitochondrial iron levels are maintained. Therefore, the low activities observed are not solely due to oxidative damage caused by excess iron. Rather, these molecular chaperones likely play a direct role in the normal assembly process of Fe/S clusters.